Building resilience by challenging social norms: integrating a transformative approach within the BRACED consortia. (4th April 2019) - McOmber, Chesney; Audia, Camilla; Crowley, Frances
Abstract : Resilience is a complex phenomenon whereby a multitude of social and environmental factors, including gender, combine to shape the ways that shocks affect people. Looking at two BRACED (Building Resilience and Adaptation to Climate Extremes and Disasters) projects, in Burkina Faso and in Ethiopia, this article uses a desk review and primary data from partners and people at risk to explore how a gender‐transformative approach can be an integral part of resilience‐building projects, particularly those implemented by multi‐stakeholder consortia. It also suggests ways to incorporate a stronger gender component in similar future projects. The article argues that donors and programme managers must provide clear principles and guidelines for achieving gender equity within resilience‐building efforts. However, these must allow flexibility to adapt to norms, needs and resources as determined by implementing partners. The right balance can be achieved by facilitating spaces for individual and collective goal‐setting; assessing current capacity and trajectories; and lesson‐sharing as an iterative process for institutional learning.